Underlining the Meaning of Law and Justice in the Era of Sustainable Development Goals (SDGs) - LesRev, Admin; Waspiah, Waspiah (Lex Scientia Law Review, 2018)
Indonesia as a developing country faces many problems and challenges, be it in social, cultural, resilience and security, education, law enforcement, health, and other aspects. The existing challenges are proof that international development is accelerating and has a significant impact on national development. One of the challenges is how to realize the goals in the era of sustainable development (sustainable development goals) or SDGs, which cover all aspects of the nation and state.